Wise Teaching to Students’ Kinesthetic Intelligence: The Teacher as Surrogate, Guru, Foreshadower, Choreographer, or Expeditionist - Sara K. Schneider (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
Based on the degree of the teacher’s perceived skill, engagement, and role play with her students, this model posits six distinct styles of teaching to students’ kinesthetic intelligence and differentiates their effects on learning.